Assessment of Rock slope Stability of the Northwestern Plunging Area of Hamrin Anticline in the Sallahaddin Governorate / Northern Iraq - Saman S. Mohammed; Mohammed R. Abood (Genius Publishing Group, 2022)
In Iraq, the majority of rock slope instability issues along highways result in road deterioration or collapse. One of these is located on the northwestern plunge of the Hamrin anticline fold. For the study of this problem, stations along the road within the Fatha Formation are selected. The study included an investigation of the slope's stability and the occurrence and potential failures. The stability of the slopes was evaluated using the SMRTool-v205 software, which is used to classify the condition and degree of slope stability. The stability analysis results demonstrate the possibility of wedge sliding occurrence in the stations (2,3, and 6), thus describing them as unstable slopes and needing important intervention. Whereas the dominant failure modes in stations (1,4,5,7, and 8 in the slope with a dip 90̊) are direct toppling and wedge sliding. Therefore, they have been described as normal and partially stable slopes and need systematic monitoring. As well, direct toppling is the dominant failure mode in the stations (2, 4, and 8), which are classified as good and stable slopes but need to be monitored occasionally.
Keywords: Slope stability; RMR; SMR; Hamrin fold